Avaliação da eficácia do LED na fotoativação de diferentes resinas compostas - Franco, Juliana de Melo (2007)
The aim of this study was to evaluate, in vitro, the efficiency of the light-curing unit LED Elipar Freelight 2 (3M ESPE) on the light-curing composites resin Filtek® Z350, Z100® e Filtek® P60 (3M ESPE), using the halogen lamp (Ultralux – Dabi Atlante) as a control. The degree of conversion of the used resin was achieved through FT-Raman spectroscopy and through microhardness test Vickers. A cilidrical aluminum mold with diameter of 5mm and a depth of 10mm was used to build the samples, which were photoactivated only once for 40s (LH) and 20s (LED) and submitted to the scrap method, according to ISO 4049:2000. Three samples were built for each group (n=3). The samples were introduced to the epoxy resine and polished with a sequence of different grades of sandpaper to be able to the microhardness test Vickers. The test was done in 48 hours (imediate) and 6 days (mediate), after the photactivation the samples were kept in an ambient temperature and lack of light. Five indentations were made in the centre and the edge of the sample, from the top to the bottom loaded with 490,3mN for 15s. The direct analysis of the degree of conversion was done with a FT-Raman spectroscopy (Bruker, model RFS 100/S, pumped by a laser Nd:YAG in 1064nm) compared with relative intensities between C=C aromatic (1610cm-1) and C=C methacrylate (1640cm-1) on the surfaces of the top and bottom of the sample. The statistic analisys tests (ANOVA, Student-Newman-Keuls, t–Student and Bonferroni) was done to determinate the possible differences, considering the factors: resin, light source, evaluation moment and surface. Comparing the intragroup (LED x LH) of microhardness Vickers in 48h, only Group 2 (Z100) showed statistics difference with a higher ammount of hardness of the LH (85,51Kg/mm2 ). In the 6 days evaluation, all the groups showed statistics difference, comparing intragroup between two light sources, which the highest ammount of microhardness (94,39Kg/mm2) was from Group 2 (Z100) when LH was applied. There was not statistics differences of the ammount of microhardness of the surfaces on the top and on the bottom, in groups 2 (Z100) e 3 (P60) when LED was applied. The ammounts of the degree of conversion of the top surface were statistically different of the bottom surfaces. All of the studied groups, although, didn´t show statistics diference between the bottom surfaces. There was not statistics difference about the degree of conversion of the groups, between the two light sources. Although, Group I (Z350) showed the lower degree of conversion (53,30Kg/mm2) on the top surface, when LH was applied comparing to the Group II (Z100) e III (P60). Based on these results, it is concluded that the increments of the composite resin of until 2.4mm of thickness is ideal to obtain ammounts of suitable microhardness in all the composites resin analysed; and the LED Elipar Freelight 2 is an alternative light source wich substitutes the halogen lamp, able to produce suitable degree of conversion in different composites resin.